Fostering Internationalization in Adult Education Graduate Programs in the United States: Opportunities for Growth - Susan Yelich Biniecki; Maja Stojanović (Educational Considerations, 2023)
Internationalization is a key element of higher education missions to prepare learners for the global dimensions of their lives and work, which are increasingly integrated. In the United States, adult education graduate programs play a vital role in the wider educational landscape, particularly because of their interconnectedness with diverse disciplines and a working learner student population. Although student and scholar mobility remain important to fostering connections, adult education graduate programs can broaden the scope of internationalization aims. This paper proposes three main opportunities for internationalization growth within adult education graduate programs: incorporating intercultural literacy in formal curricula, emphasizing a continuing professional education approach, and integrating the formal – nonformal – informal education continuum in programs. Conceptualizing efforts within these opportunity sectors can spur innovation central to internationalization initiatives.
Keywords: internationalization; adult education; higher education; graduate programs